Evaluation of mainstreaming youth-friendly health in private clinics in Malawi - Janine Barden-O'Fallon; Shara Evans; Chrissie Thakwalakwa; Witness Alfonso; Ashley Jackson (BMC, 2020)
Abstract Background High fertility rates and low modern contraceptive use put African youth and adolescents at high risk for health complications, including maternal mortality. Mainstreaming youth-friendly health services (YFHS) into existing services is one approach to improve access to reproductive health services for youth and adolescents. The objective of the evaluation was to assess the effects of a Population Services International (PSI)-sponsored YFHS training package on voluntary uptake of family planning among youth and perceptions of service quality by youth and trained healthcare providers in Malawi. Methods In 2018, a mixed-methods convergent parallel design was used to assess relevant monitoring and evaluation documents and service statistics from PSI Malawi and qualitative data on perceptions of service quality from Malawian youth and healthcare providers. The data were assessed through separate descriptive and thematic analysis and integrated to generate conclusions. Results Results show that the number of family planning clients ages 15-24 increased from 72 to 2278 per quarter during the implementation of the YFHS training packages, however, positive trends in client numbers were not sustained after youth outreach activities ended. Focus group discussions with 70 youth and adolescents indicated that clinics were perceived as providing high-quality services to youth. The main barriers to accessing the services were cost and embarrassment. Interviews with ten healthcare providers indicated that many made efforts to improve clinic accessibility and understood the barrier of cost and importance of outreach to youth and the broader community. Conclusions The findings support research showing positive effects of mainstreaming YFHS when training for healthcare staff is combined with additional YFHS programming components. Furthermore, the findings provide evidence that provider training alone, though beneficial to perceived service quality, is not sufficient to sustain increases in the number of adolescent and youth family planning clients.